FRI0162 BASELINE CHARACTERISTICS AND OUTCOMES IN PATIENTS WITH ANAEMIA IN CLINICAL STUDIES OF TOFACITINIB IN RHEUMATOID ARTHRITIS. (June 2019) - Moeller, Burkhard; Finckh, Axel; Alvaro-Gracia, Jose-Maria; Scholz, Godehard; Aletaha, Daniel; Biondo, Francesca; Strengholt, Sander; Rivas, Jose Luis; Connell, Carol A.; Shi, Harry
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: To describe the profile of patients (pts) with RA and clinically significant anaemia and the impact of treatment with tofacitinib on those with anaemia. Methods: In this post hoc analysis, data were pooled from Phase (P)2, P3 and P3b/4 studies across the tofacitinib RA clinical programme. Pts received tofacitinib 5 or 10 mg twice daily (BID) with/without background conventional synthetic disease-modifying antirheumatic drugs, or placebo (PBO). Pts with grade ≥2 anaemia (G2A; haemoglobin [Hgb] <10 g/dL) at baseline (BL) were compared with pts without G2A (Hgb ≥10 g/dL) at BL. Demographic and BL characteristics, Hgb levels and efficacy (Disease Activity Score in 28 joints, erythrocyte sedimentation rate [DAS28-4(ESR)]) at Month (M)6 and treatment-emergent adverse events (TEAEs) were summarised descriptively. Results: The proportion of pts with G2A at BL was similar for tofacitinib (3.2%, 152 of 4736 pts) and PBO (2.4%, 27 of 1125 pts) groups. Pts with G2A at BL were more often female, Asian, younger, had never smoked and had a lower body mass index (BMI) and higher C-reactive protein (CRP) and ESR vs pts without G2A at BL; RA duration was generally similar across groups (Table). Tofacitinib seemed to improve anaemia more rapidly than PBO: in pts with G2A at BL, a lower proportion of those receiving tofacitinib had G2A at M1 and M3 vs those receiving PBO (48.8% vs 75.0%, respectively, at M1 and 36.1% vs 57.1%, respectively, at M3), while the proportions were similar at M6 (28.9% vs 30.6%, respectively). In pts receiving tofacitinib, mean Hgb levels gradually increased from BL to M6 in those with G2A at BL (1.25 g/dL change), but were relatively stable in those without G2A at BL (0.15 g/dL change). In tofacitinib-treated pts, DAS28-4(ESR) scores decreased from BL to M6 by -2.40 in those with G2A at BL and -2.42 in those without G2A at BL. DAS28-4(ESR) low disease activity (≤3.2) rate at M6 was lower in tofacitinib-treated pts with G2A at BL vs those without G2A at BL (18.3% vs 28.4%, respectively). Among pts receiving tofacitinib, those with BL G2A had a higher incidence of TEAEs vs those without BL G2A in the following MedDRA system organ classes (with incidence >20% in pts who were either with or without BL G2A): gastrointestinal disorders (30.9% vs 22.5%, respectively) and infections and infestations (44.1% vs 39.0%, respectively). Conclusion: In this post hoc analysis, more pts with BL G2A were female, Asian, younger, had never smoked, and had lower BMI and elevated ESR and CRP vs those without BL G2A. G2A resolved within 6 months in most pts with RA receiving tofacitinib, while inflammation and disease activity (assessed by DAS28-4[ESR]) decreased. G2A appeared to resolve more rapidly in pts receiving tofacitinib vs those receiving PBO. These data suggest that tofacitinib for the treatment of RA can be an option for pts who have anaemia, within prescribing guidelines. 1 References: [1] US Food and Drug Administration. XELJANZ® (tofacitinib) highlights of prescribing information. Available at: http://labeling.pfizer.com/ShowLabeling.aspx?id=959 Accessed 28 January 2019. Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support was provided by Sarah Piggott of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Burkhard Moeller Consultant for: Swissmedic Human Medicines Expert Committee Member (regulatory agency), Axel Finckh Grant/research support from: Bristol-Myers Squibb, Pfizer Inc, Consultant for: AbbVie, A2Bio, Bristol-Myers Squibb, MSD, Roche, Pfizer Inc, and UCB, Jose-Maria Alvaro-Gracia Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer Inc, Roche, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer Inc, Roche, Sanofi, and UCB, Godehard Scholz: None declared, Daniel Aletaha Grant/research support from: AbbVie, Bristol-Myers Squibb, and MSD, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Medac, Merck, MSD, Pfizer Inc, Roche, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Medac, Merck, MSD, Pfizer Inc, Roche, and UCB, Francesca Biondo Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Sander Strengholt Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Jose Luis Rivas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Carol A. Connell Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Harry Shi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc